Uncovering everyday dynamics in students' perceptions of instructional quality with experience sampling. (October 2022) - Talić, Irma; Scherer, Ronny; Marsh, Herbert W.; Greiff, Samuel; Möller, Jens; Niepel, Christoph
Abstract: Within-student dynamics in perceptions of instructional quality have been neglected, although student states constitute a major share of these perceptions. The present study examined the structure and correlates of student state perceptions of the three basic dimensions, teacher support, cognitive activation, and classroom management. We conducted a three-week experience sampling study using state measures in four subjects (observations: n mathematics = 2, 681, n physics = 1, 555, n German = 2, 026, n English = 1, 835) and analyzed data from 372 German secondary school students ( M age = 15.3 years), conducting two-level confirmatory factor analyses. Against more parsimonious solutions, the postulated three-factor structure was confirmed within- and between-students across subjects, entailing 51% within-student variance on average. Similar to trait-like perceptions, state perceptions were positively related to grades and academic interest. Our results support the factorial and convergent validity of state student perceptions of instructional quality, expanding upon between-person-based literature and uncovering opportunities to enhance teaching effectiveness. Highlights: Students' perceptions of instructional quality are habitual and situation-specific. Situational state student perceptions are structured within Three Basic Dimensions. They show trait-like relations to student motivation and achievement. These perceptions operate similarly within and between students. Intensive longitudinal methods (experience sampling) reliably assess these states.